2012 IEEE 15th International Conference on Harmonics and Quality of Power 2012
DOI: 10.1109/ichqp.2012.6381296
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary techniques, a sensitivity-based approach for handling discrete variables in reactive power planning

Abstract: The paper proposes an application of an optimization evolutionary technique, improved Differential Evolution, to reactive power planning. This problem could be formulated mathematically as a nonlinear, non smooth, mixed integer, multi-objective optimization problem. The main objective deals with the minimization of the real power losses that result in a better reactive power dispatch and improving the voltage profile across the system and keeping the control variables in their operational limits. Here we use a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…Evolutionary optimization algorithm are global search techniques, thus they can overcome the drawbacks of the traditional optimization methods: in fact, they can face nonlinear and discontinuous problems, with a great number of variables [14,15]. Among the main evolutionary optimization approaches it is worth mentioning the Genetic Algorithm (GA) and the Particle Swarm Optimization (PSO).…”
Section: Gso Algorithmmentioning
confidence: 99%
“…Evolutionary optimization algorithm are global search techniques, thus they can overcome the drawbacks of the traditional optimization methods: in fact, they can face nonlinear and discontinuous problems, with a great number of variables [14,15]. Among the main evolutionary optimization approaches it is worth mentioning the Genetic Algorithm (GA) and the Particle Swarm Optimization (PSO).…”
Section: Gso Algorithmmentioning
confidence: 99%
“…The authors in [20] discussed a hierarchical reactive power planning that optimizes a set of curative controls, such that solution satisfies a given voltage stability margin. Evolutionary algorithms (EAs) Like Genetic Algorithm (GA), Differential Evolution (DE), and Evolutionary planning (EP) [19] have been extensively demoralized during the last two decades in the field of engineering optimization. They are computationally competent in result the global finest solution for reactive power planning and will not to be get attentive in local minima.…”
Section: Introductionmentioning
confidence: 99%
“…They are computationally competent in result the global finest solution for reactive power planning and will not to be get attentive in local minima. Such intelligence modified new algorithms are used for reactive power planning recent works [18,19].Despite of several positive features, it has been observed that DE sometimes does not perform as good as the expectations. Empirical analysis of DE has shown that it may stop proceeding towards a global optimum even through the population has not converged to a local optimum.…”
Section: Introductionmentioning
confidence: 99%
“…Heuristic methods often use sensitivity analysis to calculate static first order sensitivity of power loss to node reactive power under primary distribution system before installing capacitors to select the candidate buses of capacitors [11][12][13]. In a feeder line maybe there are several nodes with higher sensitivity.…”
Section: Introductionmentioning
confidence: 99%